Achalasia and chronic opiate use: innocent bystanders or associated conditions?. Issue 1 (1st January 2016) - Ravi, K.; Murray, J. A.; Geno, D. M.; Katzka, D. A.
Summary: High-resolution manometry identifies three subtypes of achalasia. However, type 3 differs from classic achalasia. Although opiates affect esophageal motility, opiate use and achalasia have not been studied. Patients with a new diagnosis of achalasia at Mayo Clinic Rochester between June 1, 2012 and January 3, 2014 were identified. Clinical records were reviewed to assess symptoms, opiate use, and therapy. Fifty-six patients with achalasia were identified, 14 (25%) were on opiates. Opiate prescription was unrelated to achalasia in all cases, with chronic back and joint pain constituting the majority. Of patients on opiates, five (36%) had type 3 achalasia compared with four (10%) not on opiates ( P = 0.02). No patients on opiates had type 1 achalasia. Clinical presentation did not differ with opiates, although those on opiates were more likely to report chest pain (39 vs. 14%, P = 0.05) and less likely to have esophageal dilation (62 vs. 82%, P = 0.13), none with greater than 5-cm diameter. Contractile vigor was greater with opiate use, with distal contractile integral of 7149 versus 2615.5 mmHg/cm/second ( P = 0.08). Treatment response was inferior on opiates, with persistent symptoms in 22% compared with 3% without opiates ( P = 0.06). Opiate use is common in type 3 achalasia, with the majority of patients on opiates. No patients on opiates were diagnosed with type 1 achalasia. Manometric findings of type 3 achalasia mimic those induced by opiates, suggesting a physiologic mechanism for opiate induced type 3 achalasia. Treatment outcome is inferior with opiates, with opiate cessation perhaps preferable. Further studies assessing opiate use and achalasia are needed.